Academic Productivity of Private University Lecturers: Analysis of the Impact of Workload, Motivation, and Institutional Support - Syaifulloh, Muhammad; Triputra, Dedi Romli; Riono, Slamet Bambang; Mulyanto, Heru; Wulandari, Anna; Utami, Suci Nur (Journal La Edusci, 2025)
This study examines the relationship between workload, motivation, institutional support, and academic productivity among lecturers in private universities. Despite the growing emphasis on research output and academic productivity in higher education institutions, private university lecturers face unique challenges that may impact their productivity. Using a quantitative approach with a cross-sectional survey design, this study collected data from 217 full-time lecturers from 7 private universities across Brebes Regency, Tegal City, and Tegal Regency. The research employed stratified random sampling and utilized validated questionnaires measuring workload dimensions, academic motivation, perceived institutional support, and academic productivity indicators. Multiple regression analysis revealed that workload has a significant negative effect on academic productivity (β = -0.342, p < 0.01), while motivation (β = 0.418, p < 0.001) and institutional support (β = 0.376, p < 0.001) both demonstrated significant positive effects. Institutional support was found to moderate the relationship between workload and productivity, suggesting that strong institutional support can mitigate the negative effects of high workload. Path analysis indicated that motivation partially mediates the relationship between institutional support and academic productivity. The findings highlight the importance of balanced workload allocation, motivational strategies, and institutional support systems in enhancing academic productivity. This research contributes to the growing literature on academic productivity determinants in private higher education institutions in Indonesia and provides practical implications for institutional policy development aimed at fostering productive academic environments.